Measuring and understanding motivation among community health workers in rural health facilities in India-a mixed method study. Issue 1 (December 2016) - Tripathy, Jaya; Goel, Sonu; Kumar, Ajay
Abstract Background Motivated human resource is the key to improve health system performance and retention of health workers. There is scanty literature on measuring motivation of health workers in India. Thus, the objective of this study was to measure and identify important aspects of health workers' motivation in North India. Methods A mixed method study design was adopted. Under the quantitative component, we interviewed randomly selected 62 community health workers (CHWs) in 18 sub-centres in two blocks of District Ambala, Haryana, India using a structured motivation scale. In-depth interviews were also carried out with 18 CHWs to explore the sources of motivation. Results The age of respondents and training in the past 12 months were found to be significantly associated with motivation. Job burnout, poor personal health, job insecurity and less career development opportunities were the individual level de-motivators, whereas not being able to fulfil family roles and poor supportive supervision were identified as environmental factors for poor motivation. Love for work, and financial incentives were individual level motivators, while community support and recognition, organizational commitment and pride, regular training were identified as environmental level motivators. Conclusion Non-financial motivators such as interpersonal relations, family support, skill and career development opportunities require more attention. Regular need-based training is essential to maintain high levels of motivation.